Resilience and personal effectiveness for social workers - Greer, Jim (Principal lecturer in social work) (Sage Publications Ltd, 2016)
This book is a straightforward guide on how to cope with the stress and pressures of today's social work environment by developing the right skills and knowledge. It will help students learn from a very early stage how to be at their best; from developing strategies to look after themselves and making the best use of supervision to the support they need to dealing with bullies and/or difficult people - all essential guidance on how to improve their health and mental well being and prepare them to manage the challenges they will face.